Space of detention : the making of a transnational gang crisis between Los Angeles and San Salvador - Zilberg, Elana, 1963- (e-Duke books scholarly collection., 2011)
An ethnographic analysis of the purported transnational gang crisis between the United States and El Salvador, based on extensive research in Los Angeles and San Salvador.